Effects of activating GABAB1 receptor on proliferation, migration, invasion and epithelial-mesenchymal transition of ovarian cancer cells - Jun Gao; Yao Gao; Shixin Lin; Xia Zou; Yukai Zhu; Xintong Chen; Hong Wan; Hong Zhu (BMC, 2020)
Abstract Objective This study aimed to explore the effects of activating GABAB1 receptor by baclofen on proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) of ovarian cancer cells. Results One hundred μmol/L, 200 μmol/L and 300 μmol/L were selected as low, medium and high baclofen concentrations respectively. Cells were divided into four groups: Control, 100 μmol/L, 200 μmol/L and 300 μmol/L. Compared with the control group, the viability, colony formation, migration and invasion of SKOV3 cells were inhibited, and the apoptosis of SKOV3 cells were enhanced significantly at 200 μmol/L and 300 μmol/L baclofen. Moreover, they changed significantly with the increase of baclofen concentration. Compared with the control group, the expression of E-cadherin and GABAB1 increased and the N-cadherin expression decreased significantly in 200 μmol/L and 300 μmol/L groups. Higher concentration of baclofen induced higher expression of E-cadherin and lower expression of N-cadherin. Conclusion Baclofen inhibited the proliferation, cloning, migration, invasion and EMT of ovarian cancer cells by activating GABAB1 receptor. These results might contribute a lot to clarify the role and possible mechanism of GABAB1 receptor in ovarian cancer.